Formation of Fe(0)-Nanoparticles via Reduction of Fe(II) Compounds by Amino Acids and Their Subsequent Oxidation to Iron Oxides - K. Klačanová; P. Fodran; P. Šimon; P. Rapta; R. Boča; V. Jorík; M. Miglierini; E. Kolek; L'. Čaplovič (Journal of Chemistry)
Iron nanoparticles were prepared by the reduction of central Fe(II) ion in the coordination compounds with amino acid ligands. The anion of the amino acid used as a ligand acted as the reducing agent. Conditions for the reduction were very mild; the temperature did not exceed 52°C, and the optimum pH was between 9.5 and 9.7. The metal iron precipitated as a mirror on the flask or as a colloid in water. Identification of the product was carried out by measuring UV/VIS spectra of the iron nanoparticles in water. The iron nanoparticles were oxidized by oxygen yielding a mixture of iron oxides. Oxidation of Fe(0) to Fe(II) took several seconds under air. The size and properties of iron oxide nanoparticles were studied by UV/VIS, TEM investigation, RTG diffractometry, Mössbauer spectroscopy, magnetometry, thermogravimetry, and GC/MS.